The awareness and behaviour’s farmer towards highly pathogenic avian influenza prevention in Tra Vinh, Vietnam - Qui, N. H.; Anh Thu, N. T.; Linh, N.T. (Diponegoro University, 2024)
Disease outbreaks are partly the direct result of the expansion of poultry flocks. To understand farmers’ behaviours, their awareness of highly pathogenic avian influenza (HPAI), the study was con ducted. A total of 150 farms in three districts of Tra Vinh Province were included. Purposive sampling was used to choose respondents who have at least 20 poultry heads and a three-year operation. Descrip tive and multiple regression analyses were used to analyze data. The findings indicated that most farm ers (65.3%) were males with an average age of 50 years. Farmers received < 100/month from poultry production. The farm scale of poultry business was less than 100 heads per farmer, and birds were reared traditionally, using by-products, floor feeding, and no automatic watering systems. Selling broil ers dominated, whereas egg sales were uncommon and were generally reserved for domestic use. In addition, farmers were aware of HPAI prevention (>90% were, poor knowledge that was not validat ed). Additionally, farmers' awareness significantly increased by the enhancement in education, training, income, and full-time employment at poultry farms. It can be concluded that the small-scale poultry farming employs traditional practices with a keen awareness of infectious diseases. However, to raise farmers' awareness, strategies should concentrate on profession, education, training, and income.